2022
DOI: 10.1155/2022/5118444
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of 7-lncRNA Signature of Epigenetic Disorders by Comprehensive Epigenetic Analysis

Abstract: The survival rate of patients with lung adenocarcinoma (LUAD) is low. This study analyzed the correlation between the expression of long noncoding RNA (lncRNA) and epigenetic alterations along with the investigation of the prognostic value of these outcomes for LUAD. Differentially expressed lncRNAs were identified based on multiomic data and positively related genes using DESeq2 in R, differentially histone-modifying genes specific to LUAD based on histone modification data, gene enhancers from information co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Depending on the transcript variant, this region spans either the transcription start site or the first exon of the gene (Nassar et al, 2023) and may have an impact on downstream transcription. FAM83A is a lncRNA whose expression is positively associated with breast cancer, lung adenocarcinoma, and colorectal cancer (Cao et al, 2022; Jin et al, 2022; Liu et al, 2021; Yu et al, 2020). Although no evidence exists which explicitly ties expression of FAM83A to prostate cancer risk or prognosis, we selected this region for analysis since DNA methylation in 8q24 was previously linked to prostate cancer risk (Barry et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the transcript variant, this region spans either the transcription start site or the first exon of the gene (Nassar et al, 2023) and may have an impact on downstream transcription. FAM83A is a lncRNA whose expression is positively associated with breast cancer, lung adenocarcinoma, and colorectal cancer (Cao et al, 2022; Jin et al, 2022; Liu et al, 2021; Yu et al, 2020). Although no evidence exists which explicitly ties expression of FAM83A to prostate cancer risk or prognosis, we selected this region for analysis since DNA methylation in 8q24 was previously linked to prostate cancer risk (Barry et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Necroptosis and ferroptosis are newly discovered programmed cell deaths recently [ 47 ]. AL161431.1 acts as an autophagy- and prognosis-relevant lncRNA in NSCLC [ 48 ], with epigenetically aberrant regulation in LUAD [ 49 ] and pancreatic adenocarcinoma [ 50 ]. In addition, AL161431.1 is linked to hypoxia status and immune microenvironment of LUAD [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that chronic lower respiratory illness mortality is enhanced by low blood vitamin C levels( Salo et al, 2022 ). A cross-sectional study manifested that serum vitamin C levels are significantly associated with fibrosis in male and overweight or obese non-alcoholic fatty liver disease patients( Cao et al, 2022 ). However, association between serum vitamin C levels and the risk of rheumatoid arthritis has not been fully studied.…”
Section: Introductionmentioning
confidence: 99%